Peningkatan Efektivitas Mesin Susu Kental Manis dengan Metode Overall Equipment Effectiveness dan Diagram Ishikawa - Sugiono, Mohammad Cipto (Universitas Suryakancana, 2021)
PT. X is an industrial company that runs in milk processing which manufactured variety products of its derivative. The problem that PT. X has are the high rate of breakdown and planned downtime that happened in sweetened condensed milk sachet filling machine, resulting a low value of availability rate in 2020. These problems can be solved by using Overall Equipment Effectiveess (OEE) method as an identification of those problems and Ishikawa’s Diagram as a proposed further improvement. The average measurement result of OEE in sweetened condensed milk sachet filling machine in the year of 2020 is 71.90%. This result shows us that the percentage of OEE still hasn’t reached the company’s target which is 75%. That low achievement of OEE is caused by one dominated factor which is the value of availability rate. According to Ishikawa’s Diagram, the main cause of the low value of availability rate are preventive maintenance, autonomous maintenance and predictive maintenance which become the cause of the recent breakdown. In conclusion, if the maintenance is done properly and thoroughly, the breakdown will certainly happen rarely, so that the value of the availability rate will also rise. PT. X adalah perusahaan industri yang bergerak di bidang pengolahan susu yang memproduksi berbagai produk turunannya. Masalah yang terjadi di PT. X adalah tingginya tingkat kerusakan dan downtime terencana yang terjadi pada mesin pengisi sachet susu kental manis, sehingga mengakibatkan rendahnya nilai availability rate pada tahun 2020. Permasalahan tersebut dapat diatasi dengan menggunakan metode Overall Equipment Effectiveess (OEE) sebagai identifikasi permasalahan tersebut. Hasil pengukuran rata-rata OEE pada mesin pengisi susu kental manis sachet tahun 2020 adalah 71,90%. Hasil ini menunjukkan bahwa persentase OEE masih belum mencapai target perusahaan yaitu 75%. Rendahnya pencapaian OEE tersebut disebabkan oleh salah satu faktor yang mendominasi yaitu nilai availability rate. Menurut diagram Ishikawa, penyebab utama rendahnya nilai tingkat ketersediaan adalah maintenance preventive, maintenance otonom, dan maintenance prediktif yang menjadi penyebab kerusakan mesin.